Liderazgo y desempeño laboral de los trabajadores en la Municipalidad Provincial de Ucayali, Contamana 2023 - Flores Rodriguez, Isabel Milagros (2024)
The present study seeks to determine the relationship between leadership and work performance of workers in the Provincial Municipality of Ucayali, Contamana 2023, for which it was decided to use an applied study and non-experimental design, in which 116 officials of that institution participated to which 2 questionnaires were applied (one for each variable) obtaining as results that about 42% and 46% of the participants mentioned that leadership is implemented almost always and always properly in the institution, this is because the vast majority of respondents indicated that the communication factor (45%), the cohesion factor (48%) and the success factor (46%) are important elements when it comes to achieving good leadership, as well as The majority of respondents rated the performance variable positively, With 50% agreeing and 43% strongly agreeing that it is developed adequately within the municipality, this is because respondents consider proactivity (49%), capacity (48%), knowledge (57%) and diligence at work (47%) as a fundamental element for good performance. Finally, it was found that there is a moderate positive correlation between the leadership variable and work performance, since a Spearman's rho coefficient was 0.643 and a significance of 0.001 was obtained.